Predlog standardov za delo etnologov v spomeniškem varstvu - Hazler, Vito (Etnolog. Nova vrsta (Ljubljana), 1998)
The article brings a concise survey of the ways ethnology is included in monument protection activities and of working methods of ethnologists who are employed in monument protection institutes. It deals with fundamental researchwork, aplicable professional and management tasks and implementation tasks. The article further deals with the significance of public presentations of professional activities, the training of specialists and especially to the use of mentors - the main condition for the professional development of conservators. The autor also draws attention to the problems caused by the uncritical transfer of methods used abroad and to the use of "modern" professional terminology which has nothing in common with the rich history of monument protection activites in Slovenia.
Keywords: ethnology; etnologija; standardi; spomeniško varstvo